1992
DOI: 10.1111/j.1151-2916.1992.tb04408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Melt Temperature on the Solidification Process of Liquid Garnets Ln3Al5O12 (Ln = Dy, Y, and Lu)

Abstract: The solidification process of liquid garnets Ln,A1,0,2 (Ln = Dy, Y, Lu) was probed by differential thermal analysis. A critical temperature r,g was evidenced in the liquid. Cooling from temperatures under rlg leads to the crystallization of the singIe garnet phase. Cooling from temperatures above rlg leads to the solidification of a mixture of perovskite LnAIO, and aluminum oxide a-Al2O3. For Ln = Y, the results are in agreement with stable and metastable phase diagrams previously proposed. The YAIO, melt was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…No changes can be seen in the patterns collected in the range of 1500-1850 • C. It can be seen from this figure that the sample lost crystallinity in the diffraction pattern collected at 1900 • C. This means that the sample had melted between 1850 • C and 1900 • C. For all spectra, Al 2 O 3 peaks and Y 2 O 3 peaks were identified using a rhomboheadral unit-cell (space group R3c, a = 4.759(0)Å and c = 12.992(0)Å) 15-17 and a cubic unit-cell (space group Ia3, a = 10.608(7)Å), [17][18][19] respectively, while YAG peaks were indexed as a cubic unit-cell (space group Ia3d, a = 12.016(3)Å). 3,12,20 Fig . 3 shows the cooling cycle of the E1 composition.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…No changes can be seen in the patterns collected in the range of 1500-1850 • C. It can be seen from this figure that the sample lost crystallinity in the diffraction pattern collected at 1900 • C. This means that the sample had melted between 1850 • C and 1900 • C. For all spectra, Al 2 O 3 peaks and Y 2 O 3 peaks were identified using a rhomboheadral unit-cell (space group R3c, a = 4.759(0)Å and c = 12.992(0)Å) 15-17 and a cubic unit-cell (space group Ia3, a = 10.608(7)Å), [17][18][19] respectively, while YAG peaks were indexed as a cubic unit-cell (space group Ia3d, a = 12.016(3)Å). 3,12,20 Fig . 3 shows the cooling cycle of the E1 composition.…”
Section: Resultsmentioning
confidence: 95%
“…They could obtain synthesized high-purity YAG and YAM phases, but they concluded that YAP is a result of reaction between YAG and YAM, where residual amounts were left even after heat treatment. Gervais et al 12 studied the solidification process of liquid YAG and YAP by differential thermal analysis (DTA) and, unlike Maier and Saviniva, 8 was investigated using X-ray diffractometry, XRD, which provided the phases existing at room temperature but not the temperature ranges of the reactions. Hence, phase evolution in Al 2 O 3 -Y 2 O 3 system was studied in situ at elevated temperatures using neutron diffractometry which provided, in real time, information on the reactions and their temperature ranges.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on the crystallization kinetics of YAG in other systems have been reported [34][35][36][37]. These studies indicate that direct synthesis of YAG is difficult due to the critical influence of the temperature-time history on crystallization pathways.…”
Section: Methodsmentioning
confidence: 96%
“…The R 2 O 3 -Al 2 O 3 (R ¼ La-Lu and Y) pseudo-binary system displays a variety of nonequilibrium phenomena, including glass formation, metastable crystallization and polyamorphism in the undercooled liquid. [1][2][3] In the R 2 O 3 -Al 2 O 3 binary system, cubic R 3 Al 5 O 12 garnet (R ¼ Eu-Lu and Y), 4,5 monoclinic R 4 Al 2 O 9 (R ¼ Nd-Lu and Y) and orthorhombic RAlO 3 (R ¼ La-Lu and Y) exist as stable phases. [6][7][8][9][10][11] RAlO 3 belongs to the perovskite family of prospective laser materials with common formula ABO 3 .…”
Section: Introductionmentioning
confidence: 99%